Pengaruh Disiplin Kerja dan Stress Kerja Serta Budaya Kerja Terhadap Kinerja Inovasi Pada Kopi Bento Yogyakarta - Yuliana, Anna; K, Kusuma Chandra (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
This study aims to examine the influence of work discipline, job stress, and organizational culture on work innovation at Kopi Bento in Yogyakarta. The study involved a total of 87 respondents. The sampling technique employed an associative approach, based on the existence of relationships among the variables under investigation. Data analysis was conducted using the SPSS software. The partial analysis results indicate that work discipline has a positive influence on innovative performance at Kopi Bento in Yogyakarta. Conversely, job stress has a negative effect on innovative performance. Meanwhile, organizational culture shows a positive impact on innovative performance. Simultaneously, work discipline, job stress, and organizational culture collectively have a positive and significant influence on innovative performance at Kopi Bento in Yogyakarta.
Keywords: Innovative Performance; Work Culture; Work Discipline; Work Stress